A mouse model of autism implicates endosome pH in the regulation of presynaptic calcium entry - Julie C. Ullman (Nature Portfolio, 2018)
The Na+/H+ exchanger NHE9 is proposed to regulate the H+ electrochemical gradient across endosomal membranes. Here, the authors find that NHE9 knockout mice show autism spectrum disorder-like behaviors and disrupted synaptic vesicle exocytosis due to impaired presynaptic calcium entry.